NOONAN SYNDROME AS RESULT OF MUTATION p. S257L OF GENE RAF1: CLINICAL CASE AND REVIEW - A. A. Bukaeva; N. P. Kotlukova; E. V. Zaklyazminskaya (Российский кардиологический журнал, 2016)
Noonan syndrome is clinically and genetically heterogenic disease caused by mutations in genes coding the proteins of universal cascade of cellular signalling Ras-MAPK. Recently, about 10 genes known, with mutations leading to the disease development. Among multiple manifestations of the syndrome most clinically and prognostically significant are disorders of cardiovascular system, including hypertrophic cardiomyopathy and pulmonary artery stenosis. In the article, a case is presented of sporadic Noonan syndrome in 5-year old child with left ventricle hypertrophy and obstruction of outgoing flow. Genetic investigation revealed mutation p. S257L of gene RAF1, occurred de novo. Appearance of mutation de novo does not lead to increased risk of the second child birth with same disease by the parents.